The Phases of Soviet Pedagogy (1931) [In Bulgarian] - S. Hessen (University of Sofia, 2016)
Almost half of century Bulgaria was a part of the Soviet Block. Since 1946-1947 the Bulgarian educational system had copied the Soviet educational system. The Bulgarian pedagogues were stressed to follow directly the sinuosity of the Soviet pedagogical thought. That's why it is of special interest to be acquainted with the phases of the early Soviet pedagogy. The paper of Sergey Hessen (in Russian Gesen), a Russian scholar, in emigration in Prague, gives such information. His paper was published in a famous Bulgarian academic journal Filosofski pregred (Philosophical Review) in 1931.